G-Ratio in hardened steel grinding with different coolants - Novak, Martin; Dolezal, Roman (Manufacturing Technology Journal, 2012)
This article deals with grinding of the hardened and tempered steel in different coolants. The G-ratio is one of the important parameters of grinding process and shows efficiency of this. The development of machining technologies is still moving forward, there are new materials and types of tool using in production and manufacturing. With a new materials usage we want better parameters of process, e. g. higher G-ratio, lower heat balance and better surface quality after machining. New types of abrasive grains that we used are based on Al2O3 - microcrystalline corundum and parameter of G-ratio and surface quality after grinding will be described in this article. For experiment were chosen three types of coolants and one of grinding wheel. We can see changes of G-ratio and surface quality during grinding at different coolants.
Keywords: Grinding; G-ratio; Microcrystalline corundum; Wear